Insulin receptor-mediated signaling regulates pluripotency markers and lineage differentiation - Manoj K. Gupta; Dario F. De Jesus; Sevim Kahraman; Ivan A. Valdez; Farnaz Shamsi; Lian Yi; Adam C. Swensen; Yu-Hua Tseng; Wei-Jun Qian; Rohit N. Kulkarni (Elsevier, 2018)
Objectives: Insulin receptor (IR)-mediated signaling is involved in the regulation of pluripotent stem cells; however, its direct effects on regulating the maintenance of pluripotency and lineage development are not fully understood. The main objective of this study is to understand the role of IR signaling in pluripotency and lineage development. Methods: To explore the role of IR signaling, we generated IR knock-out (IRKO) mouse induced pluripotent stem cells (miPSCs) from E14.5 mouse embryonic fibroblasts (MEFs) of global IRKO mice using a cocktail of four reprogramming factors: Oct4, Sox2, Klf4, cMyc. We performed pluripotency characterization and directed the differentiation of control and IRKO iPSCs into neural progenitors (ectoderm), adipocyte progenitors (mesoderm), and pancreatic beta-like cells (endoderm). We mechanistically confirmed these findings via phosphoproteomics analyses of control and IRKO iPSCs. Results: Interestingly, expression of pluripotency markers including Klf4, Lin28a, Tbx3, and cMyc were upregulated, while abundance of Oct4 and Nanog were enhanced by 4-fold and 3-fold, respectively, in IRKO iPSCs. Analyses of signaling pathways demonstrated downregulation of phospho-STAT3, p-mTor and p-Erk and an increase in the total mTor and Erk proteins in IRKO iPSCs in the basal unstimulated state. Stimulation with leukemia inhibitory factor (LIF) showed a ∼33% decrease of phospho-ERK in IRKO iPSCs. On the contrary, Erk phosphorylation was increased during in vitro spontaneous differentiation of iPSCs lacking IRs. Lineage-specific directed differentiation of the iPSCs revealed that cells lacking IR showed enhanced expression of neuronal lineage markers (Pax6, Tubb3, Ascl1 and Oligo2) while exhibiting a decrease in adipocyte (Fas, Acc, Pparγ, Fabp4, C/ebpα, and Fsp27) and pancreatic beta cell markers (Ngn3, Isl1, and Sox9). Further molecular characterization by phosphoproteomics confirmed the novel IR-mediated regulation of the global pluripotency network including several key proteins involved in diverse aspects of growth and embryonic development. Conclusion: We report, for the first time to our knowledge, the phosphoproteome of insulin, IGF1, and LIF stimulation in mouse iPSCs to reveal the importance of insulin receptor signaling for the maintenance of pluripotency and lineage determination. Keywords: Insulin receptor signaling, Pluripotency, Lineage differentiation, Adipocyte, Beta cells, Neurons, Stem cells, Phosphoproteomics, Reprogramming